Use of laparoscopic hepatectomy by recognizing disadvantages and difficulty level of operative procedure - Kawaguchi, Yoshikuni (Laparoscopic Surgery, 2018)
In a recent issue of International Journal of Surgery, Deng et al. published the results of laparoscopic hepatectomy (LH) compared with open hepatectomy (OH) for patients with hepatocellular carcinoma (1). The authors analyzed 157 patients undergoing LH and 157 patients undergoing OH using propensity score matching. The operation time was significantly shorter and the amount of estimated blood loss was significantly less in the LH group than in the OH group.